2018
DOI: 10.21037/jgo.2017.10.14
|View full text |Cite
|
Sign up to set email alerts
|

A KRAS wild type mutational status confers a survival advantage in pancreatic ductal adenocarcinoma

Abstract: Similar to previously reported studies, PDAC with a wild type mutational profile has a better prognosis with a longer OS. This improved prognosis is independent of the protocol utilized in therapy for these patients. Our findings suggest that future clinical trials in pancreatic cancer should take into consideration the presence of mutations in their pre-planned analysis when assessing the efficacy of a novel therapeutic approach. This may be a crucial factor in trial concepts and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…Moreover, Kim and colleagues reported that PDAC patients with KRAS mutations display a worse response to gemcitabine-based chemotherapy and shorter overall survival than those with KRAS wild-type [ 27 ]. Along the same lines, Windon and colleagues confirmed a survival disadvantage for KRAS mutant patients, showing that such adverse prognostic effect was independent of mismatch repair status and the specific chemotherapy regimen employed [ 28 ]. These findings warrant further investigation, as they may support new strategies for implementing precision oncology in PDAC patients.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, Kim and colleagues reported that PDAC patients with KRAS mutations display a worse response to gemcitabine-based chemotherapy and shorter overall survival than those with KRAS wild-type [ 27 ]. Along the same lines, Windon and colleagues confirmed a survival disadvantage for KRAS mutant patients, showing that such adverse prognostic effect was independent of mismatch repair status and the specific chemotherapy regimen employed [ 28 ]. These findings warrant further investigation, as they may support new strategies for implementing precision oncology in PDAC patients.…”
Section: Introductionmentioning
confidence: 98%
“…Deletion of CDKN2A and KRAS mutations were reported as adverse prognostic markers throughout a plethora of diverse malignancies . Thus, poor prognosis associated with CDKN2A deletion and KRAS activation appears as a recurrent feature of a broad spectrum of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…12 Deletion of CDKN2A and KRAS mutations were reported as adverse prognostic markers throughout a plethora of diverse malignancies. [21][22][23][24][25][26][27][28][29] Thus, poor prognosis associated with CDKN2A deletion and KRAS activation appears as a recurrent feature of a broad spectrum of malignancies. As CUP may arise from any organ site, it is plausible that these negative prognostic effects observed in other cancer entities are also reflected in CUP.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group has reported that DPYD*9A (c.85T>C) variant was the most common variant diagnosed in our cohort and a genotype-clinical phenotype correlation was noticeable. All patients who received full dose fluoropyrimidines experienced grade 3-4 diarrhea [15,16]. Other group have also reported the correlation between DPYD*9A (c.85T>C) and grade 3-4 toxicity [8,10,11].…”
Section: Editorialmentioning
confidence: 99%